Sługa Jahwe w interpretacji św. Hieronima - Jóźwiak, Magdalena (Vox Patrum, 2018)
In the history of exegesis three general models of the interpretation of the Servant of Yahweh Song can be outlined. The first one is a collective interpretation that considers the Servant to be Israel – the People of God – or its faithful part. The second interpretation was called by the scholars an individual interpretation according to which the Servant is an individual. The third one is a mixed interpretation. The Servant of Yahweh is a king who represents the nation. In this article we searched for an answer to the question who is the said Servant of Yahweh according to St. Jerome. Having analysed selected passages of St. Jerome’s commentary on the Servant Song it is not difficult to notice that the author of the Vulgate prefers the model of individual interpretation. More precisely, in his opinion the Servant of Yahweh is Jesus Christ whose suffering has a redeeming virtue.